2007
DOI: 10.1111/j.1600-0420.2007.00991.x
|View full text |Cite
|
Sign up to set email alerts
|

Visual outcome and cataract development after allogeneic stem‐cell transplantation in children

Abstract: . Purpose:  To report visual functions and prevalence of cataract after haematopoetic stem‐cell transplantation (SCT) during childhood and to determine the impact of different conditioning regimes and other possible risk factors. Methods:  Assessment of visual acuity (VA), slit‐lamp biomicroscopy of the lenses and examination of the ocular fundii were performed in 79 subjects 2–18 years (median 7 years) after SCT. Results:  Best‐corrected decimal VA ≥ 0.5 was achieved in 152/158 eyes (96%). There was an increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 13 publications
0
42
1
1
Order By: Relevance
“…Эти состояния, как правило, связаны с ТОТ, применением бусульфана и глюкокортикостероидов [83]. Синдром сухого глаза встречался в исследованиях не так часто и беспокоил 10-15 % пациентов после ТГСК с раз-витием кератоконъюнктивита [86]. Ухудшение слуха связывают с введением препаратов, препятствующих сшиванию ДНК, и высокими дозами облучения [87].…”
Section: нервная система и психоэмоциональный статусunclassified
“…Эти состояния, как правило, связаны с ТОТ, применением бусульфана и глюкокортикостероидов [83]. Синдром сухого глаза встречался в исследованиях не так часто и беспокоил 10-15 % пациентов после ТГСК с раз-витием кератоконъюнктивита [86]. Ухудшение слуха связывают с введением препаратов, препятствующих сшиванию ДНК, и высокими дозами облучения [87].…”
Section: нервная система и психоэмоциональный статусunclassified
“…Demographic data including mean age at SCT, diagnoses and gender from 79 patients have been presented previously (Fahnehjelm et al 2007(Fahnehjelm et al , 2008. Fifty-three patients (27 male and 26 female) with a median age of 15.4 years (range 7.4-20.9) underwent RB visual field examinations, all performed by one of the authors (M.O.).…”
Section: Methodsmentioning
confidence: 99%
“…In brief, there was an increased risk of cataract after conditioning with single-dose TBI (s-TBI) or fractionated TBI (f-TBI) compared to busulfan or other chemotherapy (p < 0.001) (Fahnehjelm et al 2007). Full dose f-TBI compared to s-TBI postponed but did not prevent cataract or cataract surgery while chemotherapy-based conditioning induced less severe cataracts, usually not requiring surgery (Fahnehjelm et al 2007). Epithelial superficial keratopathy was shown to be more common if the patients were exposed to repeated high trough levels of cyclosporine A (Fahnehjelm et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…33 Long-term steroid treatment following transplant, as well as the occurrence of cGVHD can accelerate cataract development. 34 Van Kempen-Harteveld et al 35 reported that shielding the eyes during TBI correlates with a decreased occurrence of cataract and an increased latency time, without increasing the risk of central nervous system relapses.…”
Section: Risk Features For Cataractmentioning
confidence: 99%